Finite element method modeling of temperature gradient-induced Cu atomic thermomigration in Cu/Sn/Cu micro solder joint. (February 2022) - Bai, Tianyue; Qiao, Yuanyuan; Wang, Xudong; Zhao, Ning
Abstract: Predicting the growth of interfacial intermetallic compounds (IMCs) under temperature gradient (TG)-induced atomic thermomigration (TM) in micro solder joint is an important aspect for improving the reliability of packaged devices. In this paper, we propose a new model based on finite element method (FEM) to simulate the Cu concentration distribution and the diffusion flux for the cold end IMC formation in Cu/Sn/Cu micro solder joints under TG with different preferred β-Sn grain orientation. It is confirmed that the orientation of β-Sn grains had a great effect on the growth rate of the cold end IMC. Meanwhile, the orientation of β-Sn grains also affected the time when the Cu concentration distribution reached a steady state, but not the final Cu concentration values at the same positions after reaching the steady state. By comparing the simulation results with the experimental data from literature, the proposed FEM model was proved to be reliable for analyzing the atomic concentration field and the diffusion flux for IMC formation in Sn-based micro solder joint under TG. Highlights: A program was designed to simulate diffusion flux for the formation of cold end IMC in Cu/Sn/Cu micro solder joints. The Cu concentration was determined from an inverse design by using the data of the IMC in reference. The effect of grain orientation on the diffusion flux for the formation of IMC was proved by simulation.